2013
DOI: 10.5812/jjnpp.7736
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of two Edible Green Seaweeds From Northern Coasts of the Persian Gulf

Abstract: A B S T R A C TBackground: Ulva genus, an edible seaweed, and an important food source in many south-east Asian countries is also recognized by its synonymous name as Enteromorpha. Objectives: This study was carried out to evaluate antioxidant activity, contents of total phenolics, and flavonoids of methanolic extracts of edible green seaweeds including Ulva clathrata (Roth) C. Agardh and three samples of Ulva prolifera O.F.Müller grown at different parts of Bushehr Province along the northern coasts of the Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
69
4
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 20 publications
12
69
4
7
Order By: Relevance
“…Antioxidant capabilities correlated significantly with phenolic content in accordance with current knowledge (Yuan and Walsh 2006;Farasat et al 2014). However antioxidant capabilities and anti-cancer abilities did not correlate well.…”
Section: Discussionsupporting
confidence: 86%
“…Antioxidant capabilities correlated significantly with phenolic content in accordance with current knowledge (Yuan and Walsh 2006;Farasat et al 2014). However antioxidant capabilities and anti-cancer abilities did not correlate well.…”
Section: Discussionsupporting
confidence: 86%
“…The genus Ulva is edible, macroscopic, parenchymatous, thread-like seaweed, and an important food source in many southeast Asian countries. Ulva is also recognized by its synonymous name as Enteromorpha (Farasat et al 2014). Padina antillarum (Kützing), Piccone and Padina boergeseni are types of fan-like brown algae (Dictyotaceae) found in the Indo-Pacific and Tropical West Africa (Wynne and Clerck 1999).…”
Section: Introductionsupporting
confidence: 92%
“…Zubia, 2009 also suggested that there three other types of antioxidant molecules structurally diverse from phenolic compounds e.g., carotenoid, terpenoid and ascorbic acid [40]. Moreover, this study found in compliance with Farasat, 2014 research result that concludes antioxidant activity of algae not only found in Rhodophyta, Phaeophyta but also have been found in Chlorophyta [41]. If phycobiliproteins are responsible for the oxidative defense of Rhodophyta, Dumay and Morançais propose that in Chlorophyta the pigment that associated with the light-harvesting is chlorophyll-binding polypeptide [32].…”
Section: Dpph Radical Scavenging Activitysupporting
confidence: 73%
“…Although sample 26 which possessed the highest value of protein content demonstrated the highest DPPH scavenging 79.27±1.81 % but only have high IC50 value. This screening confirms that the antioxidant capabilities as % antioxidant activity value were affected by the total protein content of extract with positive correlation r =0.3898, and statistically found there was a negative correlation (-0.3785) with an IC50 value the same result was found in other research [39,41]. Nevertheless, Lacerda proposes that amino acid composition and structure in the plant is liable for the antioxidant function observed [39].…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%